Massive open online course related learning style and technology usage patterns of Thai tourism professionals - Suepphong Chernbumroong (2018)
The e-learning under the concept of massive open online courses (MOOCs) was adopted as an online learning system platform called "Thailand ACCSTP online learning system" with the aim of promoting the Mutual Recognition Arrangement (MRA) of qualifications for ASEAN Tourism Professionals as knowledge workers in Thailand. However, since the system has been implemented, the completion rate is very low compared to other MOOCs. For a better completion rate and learning outcome in MOOCs, the learning style and technology usage of learners in Thailand using the ACCSTP online learning system needs to be investigated. The purpose of this research is to explore the learning styles of knowledge workers working as tourism professionals in five stars' hotels in Chiang Mai, Thailand. The total number of participants is 144, covering six divisions as follows: housekeeping, front office, food and beverages services, food production for the hotel division, travel agencies and tour operators of the travel division. Our research method was based on questionnaires consisted of two parts. The first part refers to the technology usage consisting 12 items with the aim of identifying the usage of technology devices, such as smartphones, tablets and PCs. The second part is the Index of Learning Styles (ILS) developed by Felder and Silverman (1988) that consist of 44 items. The learning style is divided into 4 dimensions. Each of the dimensions contains 11 items. Data were analyzed descriptively using the SPSS 20.0 for Windows. Results from the analysis showed that the smartphone is playing a dominant role which influences the technology usage of tourism professionals. The following learning styles could be identified as typical for the different learning dimensions: visual style for the input dimension; active style for the procession dimension; sequential style for the comprehension dimension and sensing style for the perception dimension. Based on the findings, the researchers suggest that the course designers and instructors of MOOCs should align their teaching approaches, strategies, methods and techniques with the dominant learning styles of each learning dimension.